Probiotic Lactobacillus sp. as a Substitute for Growth Antibiotic (AGP): Its Effects on Production Performance and Contribution Margin Value in Broilers Infected with Escherichia coli - Muhammad Aviv Firdaus; Soeharsono Soeharsono; Widya Paramita Lokapirnasari; Sri Hidanah; Kusnoto Kusnoto; Erma Safitri; Himatul Ilma Silfia; Ertika Fitri Lisnanti (Jurnal Ilmu-Ilmu Peternakan)
This study aimed to show that the probiotic Lactobacillus sp. could increase production performance (feed consumption, feed conversion, feed efficiency, body weight gain and body weight) and the contribution margin value in broiler chickens infected with Escherichia coli. This experimental study utilized a completely randomized design and involved 40 male broilers. The broilers were infected with Escherichia coli at the age of 21 days, and the study lasted for 35 days. The study consisted of 4 treatment groups, with 10 chickens in each group. The treatment groups were as follows: P0 (negative control; no feed additive; no E. coli infection), P1 (positive control; no feed additive; E. coli infection), P2 (AGP (zinc bacitracin) added at 1 g/kg mixed through commercial feed; no probiotic Lactobacillus sp.; E. coli infection), and P3 (commercial feed no AGP; probiotic Lactobacillus sp. added at 5 mL/L through drinking water; E. coli infection). The data were analysed via a general linear model (repeated measures) test of ANOVA followed by Duncan's multiple distance test. The results revealed significant differences (p<0,05) in production performance, including feed efficiency and final body weight. The highest contribution margin value shown by the P3 treatment group (administering probiotic Lactobacillus sp. in drinking water) was IDR 81,570, and the lowest value shown by the P2 treatment group (administering AGP to feed) was IDR 35,468. In conclusion, the addition of the probiotic Lactobacillus sp. at a concentration of 5 mL/L through drinking water improved production performance and increased the contribution margin value in broilers infected with E. coli.